(3OjhGf GdhChGA GdOeTbjs - (3eMeO Hf CMeO GdZSGfj GdOeTbj, CHh GdaQL, GdeYQha H` GdhChGA,J (B385 (3g` s ((3EOQjS Hf Ydj Hf EHQGgje GdYdhj s)
(3ChdgG (B:s
(3dh cGf efbWYG eG cGf eJUdG ajg, hefKQG eG cGf efJXeG s
(3BNQgG (B:s
(3CLaGf OQ Ydi PQj bUH JfXQ eScG heG HgG YQb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B71 - (3U(B105s
(3GdOjhGf ZjQ oeQJH Ydi GdbhGaj Ch GdehVhYGJs
(3NW GdfGSN gh NW cGJH GdeLehYIs
(3hbO ocJHJ HYV gPg GdeLehYI SfI (B999(3g``` hHYVgG SfI (B1003(3g````s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs